Phân tích mối quan hệ giữa tiêu thụ năng lượng, phát thải khí CO2 và HDI tại một số quốc gia châu Á - Trần Văn, Nguyện; Đinh Hồng, Linh; Trần Văn, Quyết (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study focus on suggesting a preferred approach to analyze the relationships among CO2 emissions, energy consumption, and HDI through using the panel data of 27 Asian countries. The main findings indicate that while higher levels of HDI require less energy consumption in higher income countries, they are linked with more energy consumption in mid-income countries in Asia. In addition, energy consumption and CO2 emissions impact insignificantly on HDI in the short run; however, they significantly contribute to the improvement of HDI in the long run. Overall, energy consumption contributes to higher environmental degradation particularly in terms of CO2 emissions and high energy consumption does not maintain higher HDI in the short run. Therefore, policymakers should consider the relationships that exist among them to create a plan for sustainable development and environmental protection.
Keywords: HDI; Energy consumption; CO2; ECM; Asia; Causality test